The geographic bias of mammal studies: a comparison of a half a century of research on Palearctic and Neotropical mammals - Guerrero-Casado, José (2021)
Introduction: There are no studies that specifically compare research output of Palearctic and Neotropical mammalogy; such comparison would be useful for informed decisions in conservation and management. Objective: To compare the scientific documents and citations about Palearctic and Neotropical mammals over half a century. Methods: We compared 50 years (1970-2019) of documents on 60 medium and large-sized (heavier than 1 kg) mammal species, in Scopus and the Web of Science (WoS) Core Collection, considering number of documents and four citation indicators at the species level (h-index, citation rate, total citations, and citations per year). Results: We retrieved 13 274 documents in Scopus and 12 913 in WoS. We found that Palearctic mammals have 3.77 times more documents than Neotropical species in Scopus (3.91 times in WoS), and that the documents recorded 5.95 more total citations in Scopus (6.93 times more in WoS). Palearctic documents also record more yearly citations and a higher h-index in both Scopus and WoS. Scopus retrieved more articles for Neotropical species (2 782 vs. 2 631 in WoS) and had more citations (28 120 vs. 24 977 in WoS); differences for the citation indicators between regions were marker in WoS. The h-index and total citations are greatly affected by how many studies are published, i.e. the region with more production is the one with higher values. The Neotropical articles showed a greater growth rate in the last decade, decreasing the gap between both regions. Conclusion: There is a regional bias in WoS and Scopus, which retrieve more articles and citations about Palearctic mammals than about Neotropical mammals; this bias is worse in WoS and means that an urgent increase in indexed research about Neotropical species is needed to be on par with Palearctic research.